2010
DOI: 10.1080/09544820802236211
|View full text |Cite
|
Sign up to set email alerts
|

Recommending a platform leveraging strategy based on the homogeneous or heterogeneous nature of a product line

Abstract: Platform-based product development depends on many factors, including technology, cost, competition, and life cycle considerations. Many companies would benefit from knowing more about the nature of their product families and how they impact platform-based product development. We assert that the development of a product platform and its derivative family of products is also impacted by the homogenous or heterogeneous nature of the products being developed, which has received little attention in previous engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Building platform-related capabilities are an important component of organizations' ability to realize platform-based product success As noted above, adopting a platform strategy will not automatically result in the achievement of certain positive goals such as cost reductions or reduction in time to market. In addition, certain negative or unachievable effects such as innovation barriers, high investment risks, or the risk of a product being too complex have been highlighted by several authors (Alizon et al 2010;Halman et al 2003;Meyer and Lehnerd 1997;Robertson and Ulrich 1998). Obviously, the existence of a platform does not guarantee success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building platform-related capabilities are an important component of organizations' ability to realize platform-based product success As noted above, adopting a platform strategy will not automatically result in the achievement of certain positive goals such as cost reductions or reduction in time to market. In addition, certain negative or unachievable effects such as innovation barriers, high investment risks, or the risk of a product being too complex have been highlighted by several authors (Alizon et al 2010;Halman et al 2003;Meyer and Lehnerd 1997;Robertson and Ulrich 1998). Obviously, the existence of a platform does not guarantee success.…”
Section: Discussionmentioning
confidence: 99%
“…Platform-based product development is targeted to maximize the use of the platform as much as possible. Several authors have focused on platform-based product development and assessment tools for product family optimization (de Weck et al 2003), a knowledge-based system for derivative products (Zha and Sriram 2006), the design of a derivative using a variation-based model (Nayak et al 2002), homogeneity or heterogeneity metrics of derivatives to estimate platform leveraging (Alizon et al 2010), and an automatic design method to develop product variants (AlGeddawy and ElMaraghy 2013). Some authors have also proposed some indices that helps guide the generation of platform-based products [e.g., the Generational Variety Index and the Coupling Index (Martin and Ishii 2002), the Penalty Vector (Fellini et al 2004) and the Design Customizability Index and the Process Customizability Index (Jiao and Tseng 2004)].…”
Section: Design Of Platform and Platform-based Product Development Thmentioning
confidence: 99%
“…Veenstra et al (2006) describe a methodology for designing product platforms to be used in the house-building industry. In addition to the above approaches to designing and developing product platforms, solution tools and methods are introduced to assist product platform design (Alizon et al, 2010;Cai et al, 2008;Kim et al, 2006;Michaelis et al, 2014;Otto and Holtta-Otto, 2007;Holtta-Otto et al, 2008;Thevenot and Simpson, 2006;Van Wie et al, 2007). For examples, Michaelis et al (2014) apply functional modeling to model integrated product platform and manufacturing system for supporting the integrated design of product platforms and manufacturing systems.…”
Section: Miscellaneous Issuesmentioning
confidence: 99%
“…With 57 percent of the studies being categorised with a focus on cost reduction, this driver is the most represented driver for platform-based product development. Several studies take a more general perspective on reductions in cost resulting from implementing platform-based product development methods (Cherubini et al 2009;Chambost, McNutt, and Stuart 2008), with multiple studies referring to aspects identical to those reported for discrete manufacturing industries (Lager 2017;Alizon, Shooter, and Simpson 2010;McIntosh et al 2010;Meyer and Dalal 2002). A major theme concerning cost reduction is the increase of product yield through various modularisation techniques.…”
Section: Cost Reductionmentioning
confidence: 99%
“…Attempting to better link business and engineering in platform-based product design, Alizon, Shooter, and Simpson (2010) addresses product family and platform configuration. Their study focuses on identifying leveraging strategies for product families based on functional similarity of derivative products and identifying the platform to build the product family around.…”
Section: Product Family and Platform Configurationmentioning
confidence: 99%